Seed Development in Groundnut - Floral Biology and Peg Development - PC NAUTIYAL, (Seed Research, 2026)
Groundnut (Arachis hypogeae L.) is a semi-determinate plant in which flowering continues for a longperiod depending on the habit group or botanical types. The inflorescence varies among different types, whereas,flower is typically papilionaceous, zygomorphic and self-pollinating (clestogamous). Since, groundnut possessesa geocarpicovary, understanding the physiology of flowering, peg and pod development are important for planningseed production. The inheritance of flower on main stem inflorescence is regulated by two sets of duplicate lociwith epistatic action, while sequential flowering is regulated by duplicate pair of recessive genes (i.e., monogenicrecessive to alternate). In Spanish type, flower appears relatively early and has a broader first flowering peak,whereas, in Virginia type flowering is delayed with multiple peaks. Floral induction is controlled by both external aswell as internal stimuli and regulates the development of reproductive primordia. The most sensitive stage forinduction of flowering is reported to be around three days prior to bloom. Further, the onset of flowering includingpeg/pod development is controlled by intricate genetic network in response to extrinsic factors, i.e., day length,temperature and intrinsic factors, i.e., hormones, and cross-talks between them, including involvement ofendogenous signaling molecules. In addition, groundnut peg has the ability to suspend its development duringthe period of soil moisture-deficit and resume pod development after the relief of stress. The geotropic nature ofpeg has a peculiar physiology to fulfill the requirement of darkness for the development of fertilized ovule into podand seed. For this purpose the peg, along with the fertilized ovary carried at the tip, penetrates the soil underoptimum moisture condition. In addition, variation in pod number in groundnut is mainly associated with timing offlowering and the initial rate of flower production. It is a well- established fact that extended exposure to hightemperature and water-deficit conditions could reduce flowering and peg numbers as well as pod formation, thuslimiting the reproductive efficiency. Such flowering behavior in groundnut results variations in maturity of pod/seedleading to seeds of different size and weight at the final harvest, and resulting in poor quality. Hence, understandingthe environmental influence on floral biology and peg development is important for quality seed production ingroundnut.